Adherencia terapéutica en pacientes con enfermedad renal crónica estadio 5 mediante seguimiento farmacoterapéutico atendidos en un hospital de Iquitos, 2023 - Rios Cachique, Sara Rosula (2025)
The research work was developed and the objectives were: Identify the sociodemographic characteristics, identify a problem related to medications through pharmacotherapeutic monitoring and evaluate the level of therapeutic adherence using the Morisky-Green Test with care in the internal medicine inpatient service at the Hospital. III-Iquitos, EsSalud, during the months of December 2023 until June 2024. The methodology that was carried out was quantitative work, observational, prospective, descriptive and transversal design; The most important results were: Problem related to medication type 5 (PRM5) with 57.5% in CKD-5 and therapeutic adherence was 67.5% and it is concluded that pharmacotherapeutic monitoring allowed improving adherence to pharmacological treatment and resolving DRPs. in patients with CKD-5 treated at Hospital III-Iquitos, EsSalud, during the months of December 2023 until June 2024.